Association between CD8+ T‐cell subsets and cardiovascular disease. (22nd February 2013) - Kolbus, D.; Ljungcrantz, I.; Andersson, L.; Hedblad, B.; Fredrikson, G. N.; Björkbacka, H.; Nilsson, J.
Abstract Background The findings of experimental studies suggest that the immune system plays a key role in atherosclerosis, but the clinical importance of different immune cells in cardiovascular disease remains poorly characterized. In this study we investigated the association between CD8+ T cells and carotid disease as well as development of cardiovascular disease events. Methods The study cohort comprised 700 subjects from the cardiovascular arm of the Malmö Diet and Cancer Study. Peripheral blood mononuclear cells, obtained at the 1991–1994 baseline investigation and stored at −140 °C, were thawed and the different CD8+ T‐cell populations analysed by flow cytometry. Baseline carotid intima–media thickness and stenosis were assessed by ultrasonography and clinical events were monitored through validated national registers. Results Subjects with a high fraction of CD8+ T cells were characterized by decreased cytokine release from activated leucocytes, metabolic signs of insulin resistance and increased incidence of coronary events; hazard ratios (95% confidence intervals) for the second and third tertiles of CD8+ T cells were 2.57 (1.16, 5.67) and 2.61 (1.19, 5, 71), respectively, in a Cox proportional hazards regression model. Correlations were found between the fraction of CD8+CD25+ T cells and the degree of carotid stenosis (r = 0.11, P < 0.01), and between the CD8+CD56−IFN‐γ+ T‐cell fraction and the degree of stenosis (r = −0.18, P < 0.005). The association between CD8+CD56−IFN‐γ+ T cells and carotid stenosis remained significant after controlling for major cardiovascular disease risk factors. Conclusion This study provides prospective clinical evidence for a role of CD8+ T cells in cardiovascular disease and suggests the existence of CD8+ T‐cell subsets with different pathological functions.